Urea application in soil: processes, losses, and alternatives—a review - Motasim, Ahmmed Md; Samsuri, Abd. Wahid; Nabayi, Abba; Akter, Amaily; Haque, Mohammad Amdadul; Abdul Sukor, Arina Shairah; Adibah, Amin Mohd. (Springer Nature, 2024)
Urea is the most used fertilizer because of its significance on world food security but it is also the toughest fertilizer to manage. It is readily available to the plant and it is vulnerable to loss in various ways, causing environmental pollution and huge economic losses. Urea application requires a sound knowledge for its effective management, which will increase its availability to plants and reduce possible losses. Ammonia ( NH3) and oxides of nitrogen (N) pollute the environment, and nitrate ( NO− 3 ) leaching alters the aquatic ecosystem, which lowers the nitrogen use efficiency (NUE) of applied urea. Nitrate-contaminated drinking water causes human and animal health risks, whereas the emission of nitrous oxide ( N2O) in the atmosphere is significant to ozone layer depletion and climate change. This review discusses the processes in the soil after urea application in the soil–plant system, which includes the loss mechanisms, and the significant factors affecting the N availability and losses. This review also shows that the judicial management of urea in soil–plant systems and maintaining the best management practices and technologies ensure sustainable agricultural development and decrease the risk of environmental contamination. Finally, the review summarizes the potential mechanisms of the applied urea in the soil with their mineralization and loss pathways and delivers the scientific reference to achieve sustainable crop production and reduce the risk of N losses.